Strategi Pembelajaran Pendidikan Pancasila Berbasis Kebhinekaan dalam Membentuk Sikap Toleransi Antar Budaya Siswa - Ibrahim Taghyirul Islam Assajidin; Dadang Sundawa; Intan Indah Megasari (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to analyze diversity-based Pancasila education learning strategies in fostering intercultural tolerance among 10th-grade students at SMAK Hidup Baru. The research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. Data validity was ensured through source and technique triangulation. The findings show that the implemented learning strategies include Project-Based Learning, heterogeneous group discussions, social case studies, diversity-based worksheets, and contextual learning approaches. These strategies encourage students to actively engage in collaborative activities and understand social diversity in everyday life. The internalization of diversity values occurs through the development of tolerant attitudes, cross-cultural interactions, mutual respect, and cooperation within heterogeneous groups. As a result, students demonstrated reduced exclusive attitudes, increased awareness and appreciation of diversity, and stronger intercultural relationships. The implementation of these learning strategies also contributed to creating a harmonious, inclusive, and supportive school environment for all students.